MEDIASI SENGKETA PERCERAIAN DI PENGADILAN AGAMA BENGKULU KELAS IA (STUDI ANALISIS PENERAPAN PERATURANMAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 1 TAHUN 2016) - Juanda, Nanang (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2017)
Mediation is a peaceful, effective, and effective means of resolving disputes and may open  broader access to the Parties  to obtain  satisfactory  and  just dispute resolution. The problem in this research is how  the application of Supreme Court Regulation  of RI. No. 1 of 2016, in optimizing  the  peace efforts in divorce  disputes in Bengkulu  Class IA Religious Court, and what  are the constraints of Mediator in conducting mediation of divorce  dispute in Bengkulu  Class IA Religious Court. Problem solving is done  through  a normative juridical  approach. To analyze  the  implementation of mediation in Religious Courts Bengkulu Class IA conducted by examining library materials or secondary data related to mediation. While the  method used  is descriptive research method analysis  of mediation theories and  the  implementation of mediation in the Religious Courts by describing the case  under  investigation,  based on the relationship between theory and reality in the field. Implementation of mediation in Bengkulu Class IA religious court, broadly divided into 4 (four) stages, namely: 1). Case registration stage, 2). Mediator stipulation  stage, 3). Implementation stage of Mediation and 4). The final stage of mediation. Factors influencing  the success of mediation in Bengkulu Class IA Religious Court are aspects of mediator, sociology aspect, psychology  aspect, moral  and  spiritual  aspect and  good  faith of the  parties.  While  the  factors  inhibiting  the  success of mediation is the  strong  desire  of the  parties  to divorce,  has  become a prolonged conflict, psychological or psychological factors, the sense of willingness  to budge.Keywords: Mediation, Peace, Divorce Dispute, Supreme Court